China's Grand Strategy Contradictory Foreign Policy? - Danner, Lukas K. (Springer International Publishing, 2018)
This book describes the main contradictions in China's actions on the world stage-peaceful vs. assertive-through a culturally informed framework that takes into account China's historical memory and political culture. The author analyzes nine cases, including the Asian Infrastructure Investment Bank (AIIB), as examples that show both China's commitment to peace and development in the region, as well as its concerted effort to introduce alternative institutions on the global stage that could challenge the hegemony of the West and Western values. Lukas K. Danner is Research Associate and Lecturer at Florida International University, USA. .